Beware the villainess! 4 - Soda Ice; Berry, (Anime adapter) (Ize Press, 2025)
"The summer festival was a roaring success. Melissa destroyed Ian at all the games and took him down a peg...but there's another trashy male lead who needs to be taught a lesson-Jake Foddebrat! When Melissa catches her brother stalking Yuri, she swears he'll get what's coming to him...at the upcoming hunting tournament!"--yenpress.com.